IMPLEMENTATION OF WIRELESS NETWORKS IN THE DHARMA KARYA SCHOOL USING WINDOWS SERVER 2003. - Jonathan Albert; Yulina Yulina,Skom, MMSI (Jurnal Sistem Informasi, 2007)
In the current era of reform, the need for information is very important, especially in business and education. Therefore, the implementation of the Wireless network technology is one of the appropriate solution for the exchange of information, both internal and external environment of an organization. With this scientific writing, hopefully can help teachers and students to obtain the desired information. The author helps to build wireless networks in schools Dharma Karya use windows 2003 server. At present the school's work in seeking information Dharma still using old methods, such as through newspapers and books. So that the information obtained is still less than complete. In completing this writing, the author helps to build wireless networks in schools Dharma Karya, to help the learning process. In this study, the authors connect with the local IP 125.161.0.1 Public IP that was obtained after the register and subscribe with your Internet Service Provider (ISP) speedy using the Windows 2003 Server. The  need for information is very important, especially in education. Authors hopes With Wireless networks built on the Dharma Karya school, then the information about education can be delivered to  the students well.